Pengaruh Rasio Keuangan terhadap Kinerja Keuangan Perusahaan Manufaktur yang Terdaftar di Bursa Efek Indonesia - Ayu Purbaningrum; Henny Setyo Lestari (J-MAS (Jurnal Manajemen dan Sains), 2022)
The purpose of this research is to conclude the impact of financial ratios on the financial performance of companies. The sample in this study are companies from the manufacturing sector listed on Indonesia Stock Exchange in 2017-20211, which total 36 companies. The sampling technique used in this study is purposive sampling and the analysis method is panel data regression. The independent variables in this study are current ratio, debt to equity ratio, total assets turnover ratio, and the control variable is firm size and firm age, with the return on assets as the dependent variable. The results show that current ratio and total assets turnover ratio have an impact on financial performance, while debt to equity ratio, firm size and firm age have no effect on financial performance.